Sleep Disorders in Early Childhood and the Development of Mental Health Problems in Adolescents: A Systematic Review of Longitudinal and Prospective Studies - Lawrence T Lam (MDPI AG, 2021)
The association between sleep problems, particularly sleep disorders, and mental health has long been studied and recognized. However, the causal relationship between sleep disorders, particularly during early childhood, on mental health problems in adolescence are yet to be established. From a preventive perspective, it is important to understand the causality of mental health problems in adolescents so that intervention measures can be derived and implemented as early as possible for maximum effectiveness. To provide more precise information on the effect of early childhood sleep disorders on mental health problems during adolescence, a systematic review was conducted on longitudinal and prospective studies reported in the literature. Following the PRISMA guidelines with an extensive search of the literature 26 studies were identified. Seven of these identified studies satisfied all selection criteria with sufficient data on the effect of early childhood sleep disorders and mental health problems in adolescence. Information was extracted and analyzed systematically from each study and tabulated. The overall results obtained from these studies indicate a significant and possible causal relationship between early childhood sleep disorders and the development of mental health problems, such as anxiety, depression, and ADHD in adolescence. These results are discussed with regards to the theoretical and practical implications as well as preventive strategies.